CUSTOMER SATISFACTION MEDIATES GREEN MARKETING AND BRAND IMAGE ON CUSTOMER PURCHASING DECISIONS AT KFC AHMAD YANI PADANG - Hendriani, Geby (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
This study aims to determine how much influence green marketing and brand image have on customer purchasing decisions through customer satisfaction as an intervening variable at KFC Ahmad Yani Padang. This study consists of two independent variables, namely green marketing and brand image and one variable of customer purchasing decisions and intervening variable customer satisfaction. The analytical method used is path analysis. The method of data collection in this study was to use a questionnaire filled out by respondents, namely KFC Ahmad Yani Padang customers. The results obtained based on the Partial Test (t test) obtained: a) there is no significant effect of green marketing on customer satisfaction at KFC Ahmad Yani Padang, b) there is a significant influence of brand image on customer satisfaction, c) there is a significant influence of green marketing on decisions purchasing, d) there is a significant influence of brand image on purchasing decisions, e) there is a significant influence of customer satisfaction on purchasing decisions, f) customer satisfaction can mediate the effect of green marketing on purchasing decisions. g) customer satisfaction cannot mediate the effect of communication on purchasing decisions.